2018
DOI: 10.1002/jcb.26597
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Ski decreased the reactive astrocytes proliferation in vitro induced by oxygen‐glucose deprivation/reoxygenation

Abstract: Glia scar is a pathological marker in late phase of brain ischemia disease, which constitutes a major physical biochemical barrier to impede axonal regrowth. Astrocytes are known to be critically involved in the formation of glial scar. However, their response to ischemia and their role in neuroprotection after central nervous system (CNS) injury are not completely clear. Recently, we have demonstrated for the first time that Ski was up-regulated in reactive astrocytes after spinal cord injury in vivo and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Under the paradigm of sublethal oxygen/glucose deprivation with subsequent reoxygenation, a reactive induction of astrocytic proliferation after reoxygenation is observed (38,39). The experimental conditions of this study differed in that the glucose/oxygen deprivation applied was permanent and no reoxygenation was performed to specifically measure the amount of cell death occurring under hypoxia and glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Under the paradigm of sublethal oxygen/glucose deprivation with subsequent reoxygenation, a reactive induction of astrocytic proliferation after reoxygenation is observed (38,39). The experimental conditions of this study differed in that the glucose/oxygen deprivation applied was permanent and no reoxygenation was performed to specifically measure the amount of cell death occurring under hypoxia and glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment with alpha-melanocyte-stimulating hormone [52] and caffeic acid [53] reduce infarct size and astrogliosis. Knockdown of Ski decreased the reactive astrocyte proliferation in vitro induced by oxygen-glucose deprivation/reoxygenation [54]. Thus, results from these studies suggest that stroke treatments are often accompanied by attenuating astrocyte proliferation or astrogliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ski, as an evolutionary conserved protein, has been reported to exist in various tissues and species, and participates in diverse cellular processes, such as cell proliferation, metastasis, transformation and tumor progressions (6). Previous studies have demonstrated that Ski plays an essential role in certain pathophysiological processes, such as wound healing and astrocyte proliferation (15,21), vascular smooth muscle cell proliferation (22,23), muscle differentiation (24,25) and liver regeneration (26). Notably, Ski, as a novel therapeutic target, has been found over expression in the development of solid tumors (27).…”
Section: Discussionmentioning
confidence: 99%
“…The EdU reagent kit (Ribobio) was also used to evaluate cell proliferation based on our previous study (15). Briefly, the OS cells were transfected with siRNA for 48 h and the medium was then changed with culture medium to continue culture for 2 and 4 days.…”
Section: Methodsmentioning
confidence: 99%